Pluralizem resnic in osvoboditev metafore v teološkem kontekstu - Trebežnik, Luka (Monitor ISH, 2022)
The article considers the question of the relationship between secularization and post-secularization. To this end, it examines the thoughts of the contemporary Italian philosopher Gianni Vattimo, recognizing an innovative evaluation of the intellectual and spiritual history of European civilization. This is manifested above all in the postulation of interpretative openness and the so-called “weak thought” (pensiero debole), which largely corresponds to our postmodern era. According to Vattimo’s interpretation, weak thought, which makes no claim to absolute and eternal truths, is a direct consequence of the incarnational kenotic event, God’s self-emptying. Just as God has given up his sovereignty, we must also, according to Vattimo, give up the old metaphysical notions of powerful truths. In this context, the article critically evaluates Vattimo’s hermeneutic thought and contrasts it with some other postmodern philosophical approaches and reflections on the death of God and his potential return.
Keywords: Krščanstvo; nihilism; Nihilizem (filozofija); postmodern Christianity; postmoderno krščanstvo; Sekularizacija (teologija); sekularization; šibka misel; teologija; Vattimo, Gianni; weak thought